THE EFFECT OF ORGANIZATIONAL VALUES ON EMPLOYEE PERFORMANCE AT THE AGAM REGENCY LAND OFFICE - Nadia Dwi Harini; Yane Putri; Syafwandi Syafwandi (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
PURPOSE - This research explores the effect of organizational values on employee performance at the Agam Regency Land Office. Organizational values are a set of principles, beliefs, and norms that guide behavior in carrying out tasks.METHODOLOGY - This research uses a quantitative approach with a survey method through distributing questionnaires to the entire population of 70 employees (total sampling). The data were analyzed using validity, reliability, classical assumption tests, and simple linear regression with the help of SPSS 25 statistical data processing applications.FINDING - The results showed that organizational values have a positive and significant effect on employee performance. The regression coefficient value of 1.261 with a significance of 0.000 indicates that an increase in organizational value directly encourages an increase in employee performance. R square of 0.803 or 80.3%, this shows that the percentage contribution of the independent variable organizational value to the dependent variable employee performance is 80.3%. While the remaining 0.197 or 19.7% is influenced by other variables outside this study such as job satisfaction, work motivation, bonuses, promotions, and other variables that are not in this study. The Agam Regency Land Office integrates organizational values into the employee performance appraisal system and conducts periodic evaluations of its application. By creating a positive work climate and supporting the application of organizational values, it is expected that employee performance can improve sustainably and consistently in supporting quality public services.